Heat and Mass Transfer Model of a Cross-flow Heat-source Tower based on the Ɛ-NTU Method - Jia Jikang; Li Nianping; Peng Jinqing; Zhang Nan; Cheng Jianlin; Cui Haijiao (Zhileng xuebao)
Based on the ?-NTU method, a heat- and mass-transfer model of a cross-flow heat-source tower was established, and the transient simulation of the model was performed using the TRNSYS simulation platform. Then, the dynamic and static characteristics of the model were validated using experimental data under different conditions. The results showed that for the outlet temperature of a heat-source tower, the static relative error was controlled within 4%, and the dynamic relative error was less than 6%. For the latent heat transfer rate, the static error was less than 5 kW. Therefore, the model can ensure high accuracy while reducing calculation complexity. As the number of working fans increased, the total heat transfer rate increased from 780 to 1060 kW, and the latent heat transfer rate increased from 317 to 433 kW. The proportion of the latent heat transfer was not affected. As the temperature of the solution that entered the tower fell from ?2.85 to ?9.09 ℃, the latent heat transfer rate of the heat source tower increased from 165 to 227 kW, and the proportion of the latent heat transfer decreased from 42% to 31%. The latent heat transfer rate gradually increased with the decrease in the solution temperature. As the flow rate of the solution decreased from 260 to 100 m3/h, the heat absorption efficiency increased from 0.26 to 0.44. The solution flow rate exerted the greatest effect on the heat absorption efficiency among all operatin g parameters. To reduce energy consumption, attention should be given to the reduction control of the solution flow under a partial-load condition.